Associations between toxoplasmosis and rheumatoid arthritis among patients in Zakho City, Kurdistan Region/Iraq - Sarwin Sultan Muhamad Mizuri; Chira A. Ramadhan; Wijdan M. S. Mero (Zanco Journal of Medical Sciences)
Background and objective: Toxoplasmosis is a zoonotic disease that can cause a wide spectrum of clinical diseases. This study aimed to investigate the association between toxoplasmosis and rheumatoid arthritis among patients, besides, to confirm the role of Toxoplasma gondii in the enhancement and modulation of autoimmune diseases such as rheumatoid arthritis.